2005
DOI: 10.1016/j.jvs.2005.05.053
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of venous thromboembolism: Adherence to guidelines and impact of physician knowledge, attitudes, and beliefs

Abstract: In this cross-section of United States hospitals, lower than anticipated use of LMWH, insufficient bridging from UFH or LMWH to warfarin, and continuation of anticoagulation after hospitalization were all problems discovered with the treatment of VTE. Physician knowledge, attitudes, and beliefs are partially responsible for the gap between actual practice and international guidelines. These results suggest that hospitals should evaluate their adherence to international VTE treatment guidelines and develop stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
60
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(63 citation statements)
references
References 28 publications
0
60
0
3
Order By: Relevance
“…5 Since approximately 30% of patients with VTE are obese, 10,11,13 our findings are applicable to a substantial number of patients. Figure 5.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…5 Since approximately 30% of patients with VTE are obese, 10,11,13 our findings are applicable to a substantial number of patients. Figure 5.…”
Section: Discussionmentioning
confidence: 86%
“…A 2005 investigation 13 that included a national sample of academic, community, and Veterans Administration hospitals compared anticoagulation treatments administered to patients with VTE with the 2001 guidelines of the American College of Chest Physicians that were in effect during the period covered by the study. The investigators reported frequent deviations from the recommended choice of drug for initial therapy, timing of discontinuation, and discharge anticoagulation regimen, but they did not analyze adherence to initial dosing guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Our study did not evaluate strategies for improving adherence, but a possible strategy, proposed in the literature, would be to improve physicians' awareness of and adherence to treatment guidelines. 17 Alternatively, an improved understanding of the factors influencing compliance may help physicians to identify vulnerable subpopulations who should be targeted for further intervention or closer monitoring. 16 Future research should investigate patients, compliance and persistence would have a significant impact on risk of recurrence.…”
mentioning
confidence: 99%
“…The most widely used of these, published by the American College of Chest Physicians (CHEST, formerly: ACCP), is referenced by physicians all over the world. Still, the lack of adherence to these guidelines is such that it has warranted a growing body of research devoted to this very problem 5, 6, 7, 8, 9. Most of the studies on the subject retrospectively observe a single setting, which, while interesting, leaves important questions as to the generalizability of their findings.…”
Section: Introductionmentioning
confidence: 99%